Impacts of Dacwah Activities of Selected Muslim Scholars on Social Media Platforms on Yoruba Muslims - Abdulsalam Daud Olalekan; Suraju Saheed Badmus (MAQOLAT: Journal of Islamic Studies, 2024)
Social media has become an integral part of Muslims' personal and public lives. Through the advancement of the Internet, Social media networks such as Facebook, Twitter, Instagram, YouTube, WhatsApp, Telegram, Tik-Tok and personal blogs have gloriously allocated space for Dacwah activities. Thus, this study aims to assess the utilization of Social media platforms by selected Yoruba Muslim scholars for Dacwah activities and the impacts they have on Yoruba Muslims. Descriptive and analytical methods of research have been employed in carrying out this research. The descriptive method assists in describing how social media platforms are utilized by selected Yoruba Muslim scholars. The analytical method helps in analyzing the content of social media post by Yoruba Muslim scholars. Participatory observation, as a research tool, is used to follow some Ducāt in order to have access to their discussions and posts as well as get information on their impacts. The paper reveals that, as a result of advance in modern information dissemination, social media has provided innovative platforms for religious leaders to spread their messages and engage with various Muslims conveniently. The paper also reveals the effectiveness of religious scholars’ message in influencing attitudes, behaviors and perceptions among their followers. The paper concludes that the role of Social media in fostering unity, promoting values, and countering misconceptions about Islam cannot be underestimated. Therefore, it is recommended that the Yoruba Muslim scholars should make strategic use of Social media positively to impacts the Nigerian Muslims by disseminating knowledge fostering unity and countering misinformation.